2018
DOI: 10.1111/coa.13127
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid inner ear disorders in 50 patients with congenital nystagmus

Abstract: Efficacy of adenoidectomy for recurrent otitis media in children previously treated with tympanostomy-tube placement. Results of parallel randomized and nonrandomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…11) In most cases, MRI is performed as the first test; however, structural abnormalities are rarely found. 12) Huang, et al 13) analyzed the presence of inner ear diseases in 50 patients with congenital nystagmus and confirmed that 17 patients had accompanying inner ear diseases, such as labyrinthine dysfunction, endolymphatic hydrops, sequelae of otitis media, and congenital hearing loss. Hence, interpreting nystagmus arising from labyrinthine disease can be challenging in patients with congenital nystagmus.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…11) In most cases, MRI is performed as the first test; however, structural abnormalities are rarely found. 12) Huang, et al 13) analyzed the presence of inner ear diseases in 50 patients with congenital nystagmus and confirmed that 17 patients had accompanying inner ear diseases, such as labyrinthine dysfunction, endolymphatic hydrops, sequelae of otitis media, and congenital hearing loss. Hence, interpreting nystagmus arising from labyrinthine disease can be challenging in patients with congenital nystagmus.…”
mentioning
confidence: 94%
“…15) Such reversed OKN mainly appears in patients with congenital nystagmus and can be accompanied by cerebellar or brainstem abnormalities acquired later. 13) However, bidirectional reversed OKN appears only in congenital nystagmus. 15) There was no mention of abnormal eye tremors in the patient's initial medical history.…”
mentioning
confidence: 99%